An investigation on factors influencing on human resources productivity - Masoumeh Seifi Divkolaii (Management Science Letters)
Human resources development is one of the most important components of any organization and detecting important factors influencing on human resources management plays essential role on the success of the firms. In this paper, we present an empirical investigation to determine different factors influencing productivity of human resources of Islamic Republic of Iran Broadcasting (IRIB) in province of Mazandaran, Iran. The study uses analytical hierarchy process (AHP) to rank 17 important factors and determines that personal characteristics were the most important factors followed by management related factors and environmental factors. In terms of personal characteristics, job satisfaction plays essential role on human resources development. In terms of managerial factors, paying attention on continuous job improvement by receiving appropriate training is the most important factor followed by welfare facilities for employees and using a system of reward/punishment in organization. Finally, in terms of environmental factors, occupational safety is number one priority followed by organizational rules and regulations.